Service quality of Islamic banks: Satisfaction, loyalty and the mediating role of trust - Razali Bin Haron; Noradilah Abdul Subar; Khairunisah Ibrahim (Islamic Economic Studies (IES), 2020)
Purpose The objective of this study is to examine the impact of PAKSERV model on customers' satisfaction, loyalty and trust in Malaysian Islamic banks. These comprehensive measures concern on the cultural dimension of service quality by focusing on the mediating role of trust in the Malaysian context. Design/methodology/approach A survey was conducted involving 401 customers of Islamic banks in the states of Kuala Lumpur and Selangor, Malaysia. The data were analyzed through exploratory factor analysis, confirmatory factor analysis and structural equation model employing AMOS 23 and SPSS 23. Findings The study found positive relationship of PAKSERV dimensions of service quality, customers' satisfaction, customers' loyalty and the mediating role of trust in enhancing customers' loyalty. This study provides new evidence on how trust can act as a partial mediation on the relationship between customers' satisfaction and customers' loyalty in the cultural context of Islamic banking in Malaysia. Practical implications The findings of this study can be used as a framework for other Islamic Financial Institutions (IFIs) in improving services to its customers. Originality/value This study contributes to the body of knowledge in enhancing the understanding on customers' satisfaction, loyalty and trust in Islamic banks in Malaysia. This study also covers a broad range of respondents, hence representing a good diversity of Islamic banks' customers.
Keywords: I43; L4; L6; 330; Islamic bank; Loyalty; PAKSERV; Satisfaction; Service quality